Reconciling home and work during lockdown: The role of organisational segmentation supplies for psychological detachment and work-home conflict - Žiedelis, Arūnas; Lazauskaitė-Zabielskė, Jurgita; Urbanavičiūtė, Ieva (Psichologija, 2021)
When the lockdown was introduced to limit the spread of the coronavirus, many employees were forced to work from home, thus facing challenges to detach from work and balance work and home responsibilities. As physical boundaries between work and non-work became non-existent, organisational norms supporting segmentation between the two domains became more important than ever before. This study aimed to examine the effect of organisational segmentation supplies for psychological detachment and work-home conflict among employees with different boundary management preferences. A sample of 172 employees from one private sector organisation responded to a questionnaire measuring segmentation supplies, segmentation preferences, psychological detachment and work-home conflict. Moderated mediation analysis revealed that segmentation supplies had a protective effect on the work-home conflict, which was partly mediated by psychological detachment. Employees’ segmentation preferences did not moderate this effect. Results show segmentation supplies by the organisation to be a valuable resource when working from home that helps to psychologically detach from work and balance work and home responsibilities even for employees who prefer to integrate work and home life.
Keywords: Psychological detachment; Segmentation preference; Segmentation supplies; Work-home conflict